Schönberg-Rezeption in Japan vor dem Zweiten Weltkrieg: eine Diskursanalyse um Schönbergs Harmonielehre - Bochmann, Minari (Die Musikforschung, 2024)
The compositional reception of the twelve-tone technique started in Japan only around 1950. However, on an aesthetic as well as a literary level, Schönberg’s music and especially his Harmonielehre had been considered in Japan for several decades. This article explores that phase by analyzing Japanese pre-war music journals, demonstrating the aesthetic and theoretical reception of twelve-tone music in Japan before the start of its compositional reception. Schönberg’s Theory of Harmony was received very selectively in the circle of the New Composers’ Society in early 1930s Japan, as the composer Shūkichi Mitsukuri advocated Schönberg’s quartal harmony (and the music of Ravel and Debussy) as a model for a genuinely Japanese harmony, while functional harmonic systems were still dominant at the Tokyo Music Academy, where Klaus Pringsheim taught until 1937.